Salient stakeholder identification process for strategic ecotourism management from the perspective of Forestry Department - Yip, Hin Wai (2014)
Stakeholder involvement in ecotourism development is essential for sustainable development as specified under the Malaysian economic transformation program. For permanent forest reserves of Peninsular Malaysia, many parties are interested to take advantage of this program as it is able to benefits them. As custodians for forest security, Forestry Departments need to take proactive step to leverage various stakeholders as this task was neither sole responsibility of the department nor responsibilities of others. This Departments needs to work closely with those institutions where strategic approach should be employed to identify, define and specify the rightful stakeholders. Engaging with salient stakeholders in ecotourism development process would increase the possibility related issues being addressed and handled strategically. Forest managers need to acquire specific skills to identify salient stakeholders from a pool of stakeholders where each organization has different interests. The main problem for most forest managers in identifying salient stakeholders is that the process was complicated to differentiate between the more salient stakeholders from the other stakeholders. The previous identification procedure was too straightforward, mainly by browsing the name list. On the other hand, by applying the salient stakeholder identification process that based on three key constructs, legitimacy, power and urgency, it is able to provide the appropriate guidance to assess and recognize the rightful salient stakeholders. The objective of this study was to evaluate stakeholder identification process used currently and determine the causal factors on this identification process. Improvement on existing stakeholder identification approach was also examined. A mail questionnaire was distributed in Forestry Departments, both at the Headquarters (Peninsular Malaysia) and state forestry departments, through the respective directors. At the same time, selected environmental-based non-government organizations were included to identify the differences on their responses on these salient stakeholders’ features. Snowball sampling was applied to get respondents from these organizations. A total of 137 respondents answered the questionnaires. They were consisted of 129 respondents from Forestry Department and eight from nongovernment organizations. From this study, based on the responses from Forestry Departments, the key constructs from pre-determined model were compared with those derived from statistical tests. Principal component analysis was employed to determine the numbers of components within each key construct and also relevancy of items within these key constructs. It was found that legitimacy was considered as priority for both pre-determined and statistically tested model. However, there was an indication that urgency was the embedded factor in this selection process but, in overall, it did not giving stronger magnitude than legitimacy. Key construct such as power was not a chosen as salient feature, even though it was considered as more influencing than the other two key constructs theoretically. For the causal of selection on salient stakeholders’ features, structural equation modelling was employed. A statistically sound acceptable model was presented due to persistent with specification errors within the variables. This model was presented as it gave an initial idea how causal factors and improvement were linked together with salient stakeholders’ features. In this model, dispositional attributes were found to be influencing the selection of salient stakeholders’ features as compared to situational attributes. Among these dispositional factors, lacking knowledge among forest managers in managing relationship with other organizations was highly agreed as one of the causes of failing to identify salient stakeholders. For the process that involved improvement of stakeholder identification, personal development as dispositional approaches was better explained the relationships with salient features and influent factor than situational approaches. Personal development included human capital strengthening to enable forest managers to be more competent in planning for ecotourism development.